Study of elastic properies of Ti3Al intermetallic compound using the ab initio calculation - Soufen, Carlos Alberto [UNESP]; Campos, Marcelo Capella de [UNESP]; Pintão, Carlos Alberto Fonzar [UNESP]; Imaizumi, Momotaro [UNESP] (Trans Tech Publications, 2014)
The elastic properties of a Ti3Al intermetallic compound were studied using full potential (FP LAPW ) with the APW+lo method. The FP-LAPW is among the most accurate band structure calculations currently available and is based on the density functional theory with general gradient approximation for the exchange and correlation potential. This method provides the structural properties of the ground state as bulk modulus, equilibrium lattice parameter, and equilibrium minimum energy, and the elastic properties as shear modulus, young modulus, Zener coefficient (anisotropy), and Poisson coefficient. The calculated elastic properties are coherent with the elastic properties of the material.
Keywords: Ab initio calculation; Elastic properties; Intermellatic compound